Community economic independence through essential oil product diversification and digital marketing in Jatijejer Village - Marisca Evalina Gondokesumo; Azminah; Dwie Retna Suryaningsih; Grace Felicia Djayapranata (University of Merdeka Malang, 2025)
Jatijejer Village has significant potential for developing essential oils from various aromatic plants. To increase the selling value of essential oil products and improve marketing effectiveness, training is needed in the diversification of essential oil derivative products and digital marketing training. This community service program aims to increase the economic independence of the Jatijejer Village community through training and mentoring in the diversification of essential oil-based products and digital marketing. The activity was implemented through participatory training, hands-on practice, and intensive mentoring in the production of derivative products, such as balms and hand sanitizers, as well as digital marketing training, including introducing marketplaces, social media, and digital promotions. Program evaluation indicated a significant improvement in participants’ knowledge and skills, with average pre-test scores of 56 percent increased to 97 percent in post-test assessments. There was an improvement in economic independence, demonstrated by the increasing variety of products, namely balms and hand sanitizers, and the start of product marketing through digital platforms. This program will be continued with the opening of the Jatijejer Essential Oil House and souvenir center, which will become an integrated tourist destination for the dissemination of knowledge and increasing sales of essential oil products.